2018
DOI: 10.1039/c8cc02930j
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable high efficiency of red emitters using Eu(iii) ternary complexes

Abstract: We have synthesized Eu(iii) ternary complexes possessing record photoluminescence yields up to 90%. This high luminescence performance resulted from the absence of quenching moieties in the Eu coordination environment and an efficient energy transfer between ligands, combined with a particular symmetry of the coordination environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…Utochnikova and Kalyakina et al introduced carboxylic acid analogues into europium(III) complexes Eu‐98 to Eu‐106 ( Scheme ). Among which the PLQY of Eu‐100 reached 90%.…”
Section: Visible Light Emission Lanthanide Complexesmentioning
confidence: 99%
“…Utochnikova and Kalyakina et al introduced carboxylic acid analogues into europium(III) complexes Eu‐98 to Eu‐106 ( Scheme ). Among which the PLQY of Eu‐100 reached 90%.…”
Section: Visible Light Emission Lanthanide Complexesmentioning
confidence: 99%
“…the study of a mononuclear nine‐coordinate europium tris complexes with two tridentate N‐benzylbenzimidazole pyridine‐2‐carboxylates and its solution in dichloromethane revealed that the change of the symmetry upon dissolution from a higher C 3 to a lower C 1 shortened the radiative lifetime, resulting in the increase of the luminescence efficiency of the europium complexes. In ref . a significant increase of the quantum yield upon addition of an neutral auxiliary ligand was observed due to the change of the coordination polyhedron from higher symmetrical distorted snub disphenoid to a lower‐symmetry distorted tricapped trigonal prism.…”
Section: Some Aspects Of the Dependence Of Luminescence On Structurementioning
confidence: 99%
“…Non-modified 1,10-phenanthrolinei sapoor emissive compound, yet, for example, ac oordination to lanthanides, turns the molecule into at riplet state photosensitizer.I nvestigationso fE u III as well as Tb III phen complexes showedt hat the ligand may act as an antenna, enhancing the fluorescenceo f the poorly absorbing lanthanide ions. [8,9,63,64] An advantage of lanthanide complexes are their sharp emission spectra, originating from shielded inner-shell 4f orbitals. [65] As their fluorescence arises from forbidden intramolecular f-f transitions,i th as al ong-lived excited-state lifetime.…”
Section: Application Of P B For Lanthanide Complexationmentioning
confidence: 99%
“…Furthermore, upon coordination to metal‐ions, some phen complexes exhibit unique photophysical properties . As a triplet state photosensitizer, phen is exploited as a light harvesting antenna for enhancing the fluorescence of poorly absorbing metal‐ions, such as Eu III or Tb III …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation